The The Effect Of The Combination Of Deep Breath Relaxation 4-7-8 Method And Classical Music On Anxiety Levels Preoperative Patients With Spinal Anesthesia - Karangan, Diva Azalia; Endarwati, Titik; Purwanti, Nunuk Sri (POLTEKKES KEMENKES YOGYAKARTA, 2024)
Patients under spinal anesthesia will remain conscious during surgery. This can lead to increased anxiety which if not treated immediately can hinder anesthesia and surgical procedures. Management of a combination of deep breath relaxation 4-7-8 method and classical music as a non-pharmacological therapy that is easily learned and applied by patients. This study to be able to determine the effect of the combination of deep breath relaxation 4-7-8 method and classical music on the anxiety level of preoperative patients with spinal anesthesia at Kardinah Hospital, Tegal City. This research is a quasy experiment using a pretest-posttest design with control group. The sampling technique used consecutive sampling with samples of preoperative patients with spinal anesthesia of 36 intervention groups and 36 comparison groups. Data analysis using the Wilcoxon test and Mann Whitney test. The results of statistical tests using the Wilcoxon test obtained results p=0.000 (<0.05) in the intervention group and p=0.071 (>0.05) in the comparison group. The results of the Mann Whitney test show a signification number p=0.000 (<0.05), so Ha is accepted. The Conclusion of the study, there is an effect of giving a combination of deep breath relaxation 4-7-8 method and classical music on the anxiety of preoperative patients with spinal anesthesia at Kardinah Hospital, Tegal City.